Handbook of contemporary religions in Brazil - Schmidt, Bettina E. (Brill Handbooks on Contemporary Religion, 2016)
The Brill Handbook of Contemporary Religions in Brazil provides an unprecedented overview of Brazil's religious landscape. It offers a full, balanced and contextualized portrait of contemporary religions in Brazil, bringing together leading scholars from both Brazil and abroad, drawing on both fieldwork and detailed reviews of the literatures. For the first time a single volume offers overviews by leading scholars of the full range of Brazilian religions, alongside more theoretically oriented discussions of relevant religious and culture themes. This Handbook's three sections present specific religions and groups of traditions, Brazilian religions in the diaspora, and issues in Brazilian religions (e.g., women, possession, politics, race and material culture).